Indicadores de sostenibilidad para la evaluación del programa hábitat rural integral implementado y aplicado por la FUNHABIT en las comunidades y recintos de intervención. - Heredia Peñaherrera, Ana Cumandá (2022)
The non-governmental organizations that work for rural development, implement and execute programs and projects in the intervention territories, which when applied generate changes, both in people and in their environment, the implementation of these programs and projects, require the use of Strategies, within this aspect, monitoring and evaluation are considered as a fundamental part, however, at present Fundación Ecuatoriana del Hábitat (Funhabit) manages indicators for each specific objective of its projects, but it does not have a system of sustainability indicators that allow you to evaluate the Integral Rural Habitat program. The present research work proposed a set of sustainability indicators that allow the integral monitoring and evaluation of the integral rural habitat program that Funhabit currently applies, through its projects in the communities and intervention sites. Five indicators associated with the components of the Integral Rural Habitat were proposed, thinking of an alternative to be able to measure the change in the people and the environment in which the institution affects and that in turn could be used by other social actors that develop similar programs.